First measurement of the Z→μ+μ- angular coefficients in the forward region of pp collisions at √s=13 TeV - Aaij, Roel; Abdelmotteleb, A. S. W.; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2022)
The first study of the angular distribution of mu(+) mu(-) pairs produced in the forward rapidity region via the Drell-Yan reaction pp -> gamma*/Z + X -> l(+) l(-) + X is presented, using data collected with the LHCb detector at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 5.1 fb(-1). The coefficients of the five leading terms in the angular distribution are determined as a function of the dimuon transverse momentum and rapidity. The results are compared to various theoretical predictions of the Z-boson production mechanism and can also be used to probe transverse-momentum-dependent parton distributions within the proton.
LHCb Collaboration: R. Aaij, S.W. Abdelmotteleb, C. Abellan Beteta, F. Abudinen, T. Ackernley, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, R. Caspary, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, J. Hu, R. Kopecna, J. Kubat, B. Leverington, P. Li, S.H. Malygina, J. Marks, R. Skuza, T.D.J. Unverzagt, U. Uwer, R. Waldi, C. Wang, J. Wang, J. Wang, J. Wang, J. Wang, M. Wang, R. Wang, Y. Wang, Z. Wang, Z. Wang, Z. Wang, L. Witola, A. Zhelezov [und viele weitere]
Im Titel ist das Plus- und das Minuszeichen jeweils hochgestellt
Gesehen am 29.01.2024